Flood plain simulation model by integration of surveying packages and GIS - Hassan Mohamad, Azrinda; Kamarudin, Md. Nor (USM, 2005)
Geographic Information Systems (GIS) are tools for managing, analyzing and displaying geographic data and data which can be related to geographic objects. The collaborating element of present day GIS and computers can benefit organizations using a GIS (combined with other data base systems) as the foundation of all its data operations. To produce an effective flood monitoring systems it is therefore highly beneficial to utilize both flood modeling and GIS technologies. This paper is focusing on development flood plain simulation model. An evaluation of this approach has been using the practical application of surveying packages and GIS software. The model includes GPS data of the flooded areas based on the spatial database created for the study area. In order to identify the potential flood risk zones, respective hydrographs have been drawn to show the occurrence for the particular area. For instance, it has been implemented for the river basin of the Gombak River in Kuala Lumpur. ArcView Software is chosen to implement the model for the reason that it’s highly relevant towards the model development. The final section of this paper, we will concentrate on visualizing spatial data using a three dimensional in providing water volume on specific flood area and obtaining the analysis on the river. Triangulated Irregular Networks (TIN) is the methodology that was used in producing the flood plain model. TIN was our working map because it provided us with elevation, which is very important when looking at water levels and cross sectional river profiles.